DECREMENTAL RESPONSE ON PROLONGED EXERCISE TEST IN A PATIENT WITH THYROTOXIC PERIODIC PARALYSIS - Ostwal, Piyush; Alshaheen, Maher (MNJ (Malang Neurology Journal), 2022)
Paralysis of acute onset often presents a diagnostic challenge for the assessing physician because of a large number of differential diagnosis and overlap of clinical features among them. Thyrotoxic periodic paralysis is an uncommon cause of acute weakness. In addition to serological tests, electromyography findings during prolonged exercise test are very helpful in confirming the diagnosis. Only a few case reports of thyrotoxic periodic paralysis have been published from Middle East and none of them have described this specific electrophysiological data. A man in his 20s presented to us with acute onset weakness in both legs which was evaluated further and found to have hypokalemia. The work up for the etiology revealed thyrotoxic status and a final diagnosis of thyrotoxic periodic paralysis was established. The prolonged exercise test performed in this patient showed typical progressive decremental respsonse with nadir at 40 minutes after the exercise.